Evaluation of a federally funded workforce development program: The Centers for Public Health Preparedness() - Sobelson, Robyn K. (Eval Program Plann, 2013)
The Centers for Public Health Preparedness (CPHP) program was a five-year cooperative agreement funded by the Centers for Disease Control and Prevention (CDC). The program was initiated in 2004 to strengthen terrorism and emergency preparedness by linking academic expertise to state and local health agency needs. The purposes of the evaluation study were to identify the results achieved by the Centers and inform program planning for future programs. The evaluation was summative and retrospective in its design and focused on the aggregate outcomes of the CPHP program. The evaluation results indicated progress was achieved on program goals related to development of new training products, training members of the public health workforce, and expansion of partnerships between accredited schools of public health and state and local public health departments. Evaluation results, as well as methodological insights gleaned during the planning and conduct of the CPHP evaluation, were used to inform the design of the next iteration of the CPHP Program, the Preparedness and Emergency Response Learning Centers (PERLC).